Closing the gap: finding productive uses for vacant land in north St. Louis, Missouri - Runde, Scott (Kansas State University, 2011)
Inner city areas of many major American cities have fallen victim to “urban decay.” In many instances the result is abandonment. Nevertheless, the inner city can be redeveloped by landscape architects and others to provide a place to live, work, learn, and play while displaying sensitivity to the environment. Such developments can be wisely designed by following planning/design guidelines that follow sustainable design principles. The neighborhoods of the 5th Ward in St. Louis, Missouri are the victims of an aging industrial city. Many neighborhoods are troubled with socio-economic problems such as unemployment, low housing values, lack of educational services, scarcity of fresh, reasonably priced food, and elevated crime rates. The socio-economic problems listed above have been major factors in extensive depopulation and disinvestment since the mid 20th-century. “Today, as never before, conditions are ripe for parks to reenter the urban planning agenda. This opportunity exists because so much inner-city land that was once actively used now lies fallow and can be reused for intelligently planned parks, because so much suburban land has been developed without adequate public open space that there is now a huge suburban constituency to support park development, and because so much undeveloped land is now subject to recently enacted legislation intended to protect the environment.” (Garvin 1996, 30) The overall goal for this project is to create a productive uses for the 5th Ward’s vacant land in order to encourage economic and social growth. This can be achieved through investments in urban agriculture and accessible community space. This project serves as a potential solution for renewal of lost urban community infrastructure that includes parks and agricultural cropland. Implementing recreation and urban agriculture on vacant land could help spawn a rebirth and sustain a vibrant and economically-viable community fabric.
Keywords: Urban Agriculture; Urban Planning; Urban Renewal; Parks and Recreation; Urban Planning (0999)